OPTIMALISASI KINERJA PERANGKAT DESA DI DESA TEGALREJO KECAMATAN PONCOWARNO KABUPATEN KEBUMEN - Misdal, Misdal; Widiastuti, Nur; Hamid, Muda Setia (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2025)
Village governments are responsible for managing rural communities in accordance with national regulations, led by a village head and supported by village apparatus. This study examines the issue of suboptimal performance among the village apparatus in Tegalrejo Village, Poncowarno Subdistrict, Kebumen Regency. Using a qualitative descriptive approach with nine village apparatus as informants, data were collected through observation, interviews, and documentation. The findings show that the performance of the village apparatus is influenced by several factors, including the leadership of the village head, the educational background of the apparatus, and their work experience. Efforts to improve performance include strengthening teamwork, increasing discipline and motivation, providing training, and improving budgeting. The study recommends that the village apparatus enhance service quality and responsibility toward village development, while the village head should continue strengthening supportive factors and communication to improve overall performance.